Design of Power Supply “Electronic Center” at Kr. Baruna Jaya 8 Using Photovoltaic-Battery Hybrid System - Soedibyo, Soedibyo; Hidayat, Ainur Rachmad; Sahrin, Alfin; Wati, Trisna (JAVA Journal of Electrical and Electronics Engineering, 2015)
The utilization of solar energy as an alternative energy to generate electricity using photovoltaic (PV) connected to the grid / battery that is still working through the night has been developed in Indonesia. The use of these technologies can be done anywhere, one of which can be applied in the maritime industry. There is a electronic center room at KR. Baruna Jaya 8 that requires electric power supply continuously. Electronic Center must still be fed from the battery in the worst conditions or blackout occurs to get the delay time to turn off all the equipment and securing data. The room is supplied from the distribution panel of electronic center with a capacity of 30 kVA, 230V, 50 Hz which will redesign using PV systems - Battery. PV is connected to an inverter that can supply the power needs in the Electronic Center room. The results of simulation using PSIM software shows that the PV system can generate 25.5 kW of supply the distribution panel of Electronic Center as a substituent of fossil fuel power plants that used previously.